Risk Factors for 30-Day Mortality in Nosocomial Enterococcal Bloodstream Infections - Verena Zerbato; Riccardo Pol; Gianfranco Sanson; Daniel Alexandru Suru; Eugenio Pin; Vanessa Tabolli; Jacopo Monticelli; Marina Busetti; Dan Alexandru Toc; Lory Saveria Crocè; Roberto Luzzati; Stefano Di Bella (MDPI AG, 2024)
Enterococci commonly cause nosocomial bloodstream infections (BSIs), and the global incidence of vancomycin-resistant enterococci (VRE) BSIs is rising. This study aimed to assess the risk factors for enterococcal BSIs and 30-day mortality, stratified by Enterococcus species, vancomycin resistance, and treatment appropriateness. We conducted a retrospective cohort study (2014-2021) including all hospitalized adult patients with at least one blood culture positive for Enterococcus faecalis or Enterococcus faecium. We included 584 patients with enterococcal BSI: 93 were attributed to vancomycin-resistant E. faecium. The overall 30-day mortality was 27.5%; higher in cases of BSI due to vancomycin-resistant E. faecium (36.6%) and vancomycin-sensitive E. faecium (31.8%) compared to E. faecalis BSIs (23.2%) (p = 0.016). This result was confirmed by multivariable Cox analysis. Independent predictors of increased mortality included the PITT score, complicated bacteremia, and age (HR = 1.269, p < 0.001; HR = 1.818, p < 0.001; HR = 1.022, p = 0.005, respectively). Conversely, male gender, consultation with infectious disease (ID) specialists, and appropriate treatment were associated with reduced mortality (HR = 0.666, p = 0.014; HR = 0.504, p < 0.001; HR = 0.682, p = 0.026, respectively). In conclusion, vancomycin-resistant E. faecium bacteremia is independently associated with a higher risk of 30-day mortality.